2021
DOI: 10.14715/cmb/2021.67.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of MRI-DWI signal intensity value combined with serum PGI, PGII and CA199 in early gastric cancer

Abstract: To explore the diagnostic value of MRI-DWI signal intensity value combined with serum PGI. PGII and CA199 in early gastric cancer. Sixty cases of gastric cancer patients admitted to our hospital from December 2019 to December 2020 were selected as the gastric cancer group and 80 cases of healthy volunteers who underwent physical examination in our hospital during the same period were selected as the healthy group. All the 60 patients underwent MRI-DWI examination, and the pathological diagnosis results were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…De- γ -carboxyprothrombin (DCP) also showed good diagnostic performance for early PHC [ 16 ]. In the study of early gastric cancer diagnosis, the combined diagnostic performance of MRI-DWI signal intensity value and serum indicators such as CA199 is better than the diagnostic performance of indicators alone [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…De- γ -carboxyprothrombin (DCP) also showed good diagnostic performance for early PHC [ 16 ]. In the study of early gastric cancer diagnosis, the combined diagnostic performance of MRI-DWI signal intensity value and serum indicators such as CA199 is better than the diagnostic performance of indicators alone [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…CA199 belongs to ganglioside, and its level in the normal body is deficient. It has been confirmed that its expression is significantly increased in malignant tumours of the digestive tract, such as gastric cancer, cholangiocarcinoma and colorectal cancer 23–25 . CA125 is a glycoprotein‐related antigen that is mainly synthesized by epithelial cells.…”
Section: Discussionmentioning
confidence: 97%
“…It has been confirmed that its expression is significantly increased in malignant tumours of the digestive tract, such as gastric cancer, cholangiocarcinoma and colorectal cancer. 23 , 24 , 25 CA125 is a glycoprotein‐related antigen that is mainly synthesized by epithelial cells. Under normal physiological conditions, due to the blocking effect of the cell basement membrane, CA125 is only stored in the cells and cannot actively enter the blood circulation, which leads to relatively low levels of CA125 in normal people 26 ; however, after the occurrence of tumours, the basement membrane of the body's cells is damaged, which can cause a large amount of CA125 to enter the blood circulation, and eventually lead to an abnormal increase in serum CA125 levels.…”
Section: Discussionmentioning
confidence: 99%